GNDT II level approach for seismic vulnerability assessment of Unreinforced Masonry (URM) building stock - Shakya, Manjip (Journal of Science and Engineering, 2015)
Unreinforced Masonry (URM) structures, such as historic buildings, traditional buildings and ordinary buildings, exist all over the world and constitute a relevant part of the cultural heritage of humanity. Their protection against earthquakes is a topic of great concern among the earthquake engineering research community. This concern mainly arises from the strong damage or complete loss suffered by these types of structures when subjected to earthquake and also from the need and interest to preserve them as a built heritage. This paper initially presents a methodology for assessing the seismic vulnerability of URM buildings based on vulnerability index evaluation approach. Moreover, this paper presents the correlation between vulnerability index and Macroseismic method to estimate the physical damage in relationship with seismic intensity. Finally, presents implementation of the methodology to construct vulnerability curves, fragility curves and estimate losses.